Impact of Headline‘s Negativity and Mood on the Reaction of Readers - Švėgždaitė, Raminta (Žurnalistikos tyrimai, 2017)
The article discusses the importance of headlines in contemporary Lithuanian internet news media, impact of the headlines on formation of the attitudes of the readers. As the result of high competitiveness, the attractiveness of the headlines plays even more important role in the internet media than in traditional newspapers and magazines. The new media provides the innovative methods for readership research: measuring comments, “reads” and “sharings” of online articles enables to measure popularity of the publications and to some extend the “effectiveness” of the headlines. The current article presents the results of pilot research of two most popular Lithuanian news portals (delfi.lt ir 15min.lt). The author compares local and international news headlines in the portals. Evaluating the headlines negativity (negative, positive, neutral) and mood (dramatic, controversial, positive, neutral) enables to demonstrate the impact of news headlines on the activity of the readers. Negative and controversial news headlines encourages readers’ activity (comments and “sharings”). This tendency is more evident in the international news presentation than in local. In the context of fierce media competition efforts to generate greater readers’ activity could become the source of negativity and reporting controversy.
Keywords: headline; negativity; mood; internet media